Increasing the Efficiency of Microprocessors in an Access Control Systems - G. Magomedov, S.; ., .; ., . (International Journal of Engineering and Technology, 2018)
This paper is devoted to the problem of improving the performance of microprocessors used in access control systems. The requirements are described, and a set of commands is proposed, that are necessary for efficient design of microprocessors working on the basis of the residue number system for the purpose of monitoring and access control. The proposed approach is aimed at improving the efficiency of microprocessor operation as part of the access control system.Â Â